Cellular Bone Matrix in Spine Surgery – Are They Worth the Risk: A Systematic Review - Lambrechts, Mark J.; Issa, Tariq Z.; Mazmudar, Aditya; Lee, Yunsoo; Toci, Gregory R.; D’Antonio, Nicholas D.; Schilken, Meghan; Lingenfelter, Kenneth; Kepler, Christopher K.; Schroeder, Gregory D.; Vaccaro, Alexander R. (Global spine journal, 2024)
Study Design Systematic Review. Objective To review the literature for complications and outcomes after the implantation of cellular bone matrix (CBM) during spine fusion. Methods The PubMed database was queried from inception to January 31, 2023 for any articles that discussed the role of and identified a specific CBM in spinal fusion procedures. Adverse events, reoperations, methods, and fusion rates were collected from all studies and reported. Results Six hundred articles were identified, of which 19 were included that reported outcomes of 7 different CBM products. Seven studies evaluated lumbar fusion, 11 evaluated cervical fusion, and 1 study reported adverse events of a single CBM product. Only 4 studies were comparative studies while others were limited to case series. Fusion rates ranged from 68% to 98.7% in the lumbar spine and 87% to 100% in the cervical spine, although criteria for radiographic fusion was variable. While 7 studies reported no adverse events, there was no strict consensus on what constituted a complication. One study reported catastrophic disseminated tuberculosis from donor contaminated CBM. The authors of 14 studies had conflicts of interest with either the manufacturer or distributor for their analyzed CBM. Conclusions Current evidence regarding the use of cellular bone matrix as an osteobiologic during spine surgery is weak and limited to low-grade non-comparative studies subject to industry funding. While reported fusion rates are high, the risk of severe complications should not be overlooked. Further large clinical trials are required to elucidate whether the CBMs offer any benefits that outweigh the risks.